Evaluation of seaweed extracts functionality as post-harvest treatment for minimally processed Fuji apples. (February 2016) - Augusto, Ana; Simões, Tiago; Pedrosa, Rui; Silva, Susana F.J.
Abstract: The potential application of Fucus spiralis, Bifurcaria bifurcata, Codium tomentosum and Codium vermilara extracts as post-harvest treatments in minimally processed (MP) Fuji apple was investigated. 0.5% solutions of each extract were applied to MP Fuji apple and its effect on product quality was assessed over 20 days of storage at 4 ± 2 °C in terms of moisture content, soluble solids concentration (SSC), firmness, browning index (BI) and POD and PPO activities. Application of Codium tomentosum extract resulted in a significant reduction in BI in comparison to all other tested treatments. POD and PPO activities were also significantly lower in MP apple treated with Codium tomentosum extract. These results identify Codium tomentosum extract functionality of reducing enzymatic browning, suggesting the potential application of this extract as a natural additive in MP fruit. Industrial relevance: This study shows the advantages of using a novel post-harvest treatment based in edible seaweed extracts to preserve fresh-cut fruits, in particular Fuji apple. The results show clearly that this type of dipping treatment decreases browning index and inhibits enzymatic activities when compared with citric acid and control treatment (water). Codium tomentosum extract solution showed the highest efficacy, suggesting the potential application of this extract as a natural additive to be a substitute of chemicals used in food industry and its use has been restricted. This process is efficient, versatile and of simple implementation at the industrial level once the only change in the industrial process consists in the type of post-harvest solution treatment. Associated to the easy adaptation in the industrial process, the exponential development in aquaculture sector allows the obtention of this raw material in a sustained way. Extract functionality was attributed to its demarked inhibitory action on enzymatic activities of polyphenol oxidase and peroxidase, two major enzymes involved in enzymatic browning processes. Highlights: Edible seaweeds are a sustainable and cost effective source of compounds of interest. Seaweeds extracts are a potential natural antibrowning agent for post-harvest treatments of MP fruits. Codium tomentosum extract significantly inhibited PPO and POD activity in MP apple minimizing product browning.